Future Communication Technologies: Innovation and Impact on Global Society - Sianipar, JF.; Toruan, Tahan Samuel Lumban; Anwar, Syaiful; Aritonang, Sovian (UNIVERSITAS PAKUAN, 2025)
Development technology communication Keep going experience significant acceleration, changing method man interact , work , and live life everyday. This article discuss various technology future communication is in progress developed, including 6G network, communication quantum, internet visible eyes, reality mixed reality and holograms. With integrate analysis technology, impact social, economic, and ethical, articles This give outlook about How innovation This can change global society, as well as possible challenges and opportunities appear. Development technology communication Keep going experience significant acceleration , changing method man interact, work, and live life everyday. This article discuss various technology future communication is in progress developed, including 6G network, communication quantum, internet visible eyes, reality mixed reality and holograms. With integrate analysis technology, impact social, economic, and ethical, articles This give information about How innovation This can change global society , as well as possible challenges and opportunities appear.